Nuclear envelope rupture and NET formation is driven by PKCα-mediated lamin B disassembly - Li, Yubin; Li, Minghui; Weigel, Bettina; Mall, Moritz; Werth, Victoria P; Liu, Ming-Lin (EMBO reports, 2020)
Abstract The nuclear lamina is essential for the structural integration of the nuclear envelope. Nuclear envelope rupture and chromatin externalization is a hallmark of the formation of neutrophil extracellular traps (NETs). NET release was described as a cellular lysis process; however, this notion has been questioned recently. Here, we report that during NET formation, nuclear lamin B is not fragmented by destructive proteolysis, but rather disassembled into intact full-length molecules. Furthermore, we demonstrate that nuclear translocation of PKCα, which serves as the kinase to induce lamin B phosphorylation and disassembly, results in nuclear envelope rupture. Decreasing lamin B phosphorylation by PKCα inhibition, genetic deletion, or by mutating the PKCα consensus sites on lamin B attenuates extracellular trap formation. In addition, strengthening the nuclear envelope by lamin B overexpression attenuates NET release in vivo and reduces levels of NET-associated inflammatory cytokines in UVB-irradiated skin of lamin B transgenic mice. Our findings advance the mechanistic understanding of NET formation by showing that PKCα-mediated lamin B phosphorylation drives nuclear envelope rupture for chromatin release in neutrophils.